Comparison of Different Extraction Processes on the Physicochemical Properties, Nutritional Components and Antioxidant Ability of Xanthoceras sorbifolia Bunge Kernel Oil - Yuling Zheng; Pan Gao; Shu Wang; Yuling Ruan; Wu Zhong; Chuanrong Hu; Dongping He (Molecules, 2022)
In this study, we investigated and compared the oil yield, physicochemical properties, fatty acid composition, nutrient content, and antioxidant ability of Xanthoceras sorbifolia Bunge (X. sorbifolia) kernel oils obtained by cold-pressing (CP), hexane extraction (HE), aqueous enzymatic extraction (AEE), and supercritical fluid extraction (SFE). The results indicated that X. sorbifolia oil contained a high percentage of monounsaturated fatty acids (49.31–50.38%), especially oleic acid (30.73–30.98%) and nervonic acid (2.73–3.09%) and that the extraction methods had little effect on the composition and content of fatty acids. X. sorbifolia oil is an excellent source of nervonic acid. Additionally, the HE method resulted in the highest oil yield (98.04%), oxidation stability index (9.20 h), tocopherol content (530.15 mg/kg) and sterol content (2104.07 mg/kg). The DPPH scavenging activity rates of the oil produced by SFE was the highest. Considering the health and nutritional value of oils, HE is a promising method for X. sorbifolia oil processing. According to multiple linear regression analysis, the antioxidant capacity of the oil was negatively correlated with sterol and stearic acid content and positively correlated with linoleic acid, arachidic acid and polyunsaturated fatty acid content. This information is important for improving the nutritional value and industrial production of X. sorbifolia.